Pemanfaatan Sampah Plastik Multilayer, Styrofoam dan Oli Bekas untuk Pembuatan Paving Block - Royani; Fadlilah, Ilma; Pramita, Ayu (Talenta Publisher (Universitas Sumatera Utara), 2025)
Plastic is an essential material in our daily lives. This study identifies that among various types of waste, multilayer plastic and styrofoam are one of the most difficult to manage optimally. One alternative to reduce this problem is to use waste as a mixture material for paving blocks. The composition of multilayer plastic and styrofoam used in this study were 65%:35%, 55%:45%, 45%:55%, and 35%:65%.This research only produced paving block samples that passed the visual test, size test, and average water absorption test. However, none of the samples passed the compressive strength, abrasion resistance, and sodium sulfate resistance tests according to the SNI 03-0691-1996 standards. Meanwhile, the water absorption test results for the 65%:35% and 55%:45% multilayer plastic-styrofoam samples met the quality standard C (for pedestrian use), while the 45%:55% and 35%:65% samples met the quality standard B (for parking equipment use).